2012
DOI: 10.1007/s10763-012-9338-z
|View full text |Cite
|
Sign up to set email alerts
|

High School Students’ Proficiency and Confidence Levels in Displaying Their Understanding of Basic Electrolysis Concepts

Abstract: This study was conducted with 330 Form 4 (grade 10) students (aged 15-16 years) who were involved in a course of instruction on electrolysis concepts. The main purpose of this study was to (1) to assess high school chemistry students' understanding of 19 major principles of electrolysis using a recently developed two-tier multiple-choice diagnostic instrument, the Electrolysis Diagnostic Instrument, EDI, and (2) to assess students' confidence levels in displaying their knowledge and understanding of these elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
4
21
0
1
Order By: Relevance
“…In terms of the reasoning element, Table 1 shows that the element is mainly used at the macro-level (58.52% in individual argumentation and 40% in group argumentation). This shows that students could only construct simple arguments and lacked the ability to provide explanations at the sub-micro and symbolic levels, which is in line with the conclusions made by Dawson and Venville (2009), Heng et al (2012) and Sia, Treagust and Chandrasegaran (2012). This may be due to the low exposure to different levels of representations in science classes, causing students to learn chemistry concepts at the three levels separately and in a discrete manner (Treagust, Chittleborough & Mamiala, 2003).…”
Section: Scientifi C Argumentation Elements Constructed By Students Esupporting
confidence: 77%
“…In terms of the reasoning element, Table 1 shows that the element is mainly used at the macro-level (58.52% in individual argumentation and 40% in group argumentation). This shows that students could only construct simple arguments and lacked the ability to provide explanations at the sub-micro and symbolic levels, which is in line with the conclusions made by Dawson and Venville (2009), Heng et al (2012) and Sia, Treagust and Chandrasegaran (2012). This may be due to the low exposure to different levels of representations in science classes, causing students to learn chemistry concepts at the three levels separately and in a discrete manner (Treagust, Chittleborough & Mamiala, 2003).…”
Section: Scientifi C Argumentation Elements Constructed By Students Esupporting
confidence: 77%
“…2011 Rahayu et al [19] Indonesian and Japanese senior high-school students' understanding of: (a) reactions occurring during electrolysis; (b) differences between electrolytic and voltaic (galvanic) cells; (c) movement of ions in electrolytic cells; (d) poles in electrolytic cells; (e) electrolytic cell reactions. 2012 Sia, Treagust and Chandrasegaran [20] Students' understanding of 19 major principles of electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Using a two-tier multiple-choice diagnostic instrument, Sia, Treagust and Chandrasegaran conducted a study with 10 thgrade students, with the focus on student understanding of 19 major principles of electrolysis. [20] It was reported that the students displayed limited understanding of the electrolytic processes involving molten compounds and aqueous solutions of compounds. Although the students were found to possess relevant content knowledge, they could not provide suitable explanations for the changes that had occurred.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the limitations of multiple-choice tests, and the challenges of using tools such as interviews and open-ended questions, science educators have developed a new model of assessment called two-tier tests (Haslam & Treagust, 1987;Hudson & Treagust, 2013;Odom & Barrow, 1995;Sia, Treagust, & Chandrasegaran, 2012;Tamir, 1989;Tan et al, 2002;Treagust, 1986;Voska & Heikkinen, 2000;Wandersee, 1983). These types of assessments are advantageous because they ensure the reliability and efficiency of multiple-choice assessments, as well as the capability to diagnose student understanding and reasoning at a deeper level.…”
Section: Introductionmentioning
confidence: 99%